UI/UX SISTEM INFORMASI PRODUKSI HARIAN BERBASIS WEB MENGGUNAKAN METODE PROTOTYPE PADA PT DAW SON INDONESIA - Dewi Eldiana Zahra; Aris Nurhindarto; Indra Gamayanto; MY Teguh Sulistyono (LPPM Universitas Abdurrab, 2026)
Daily production data recording at PT Daw Son Indonesia is currently carried out using paper-based media and manual spreadsheets, leading to information delays, human error risks, and a lack of real-time monitoring. This study aims to design and develop a web-based, integrated production reporting information system to support tactical management decision-making. The system development explicitly utilized the Prototype method, emphasizing an iterative cycle with users to ensure functional alignment. The application was developed using the PHP programming language and a MySQL database. Functional testing was performed using the Black Box Testing method in a standardized environment. The test results demonstrated a system success rate of 94.44% (17 out of 18 scenarios met), where role-based authentication modules, production data management (CRUD), automated achievement calculations, and security protection against SQL Injection and XSS vulnerabilities functioned optimally according to specifications. Overall, this information system is declared highly feasible for implementation to enhance operational efficiency, guarantee daily data accuracy, and accelerate manufacturing trend monitoring at PT Daw Son Indonesia.